PENGARUH HARGA KOMODITAS PANGAN TERHADAP INFLASI DI KOTA MALANG TAHUN 2011-2016 - Rizaldy, Dicky Zunifar (Jurnal Ekonomi Pembangunan, 2017)
This research was proposed to know the effect of food commodity prices on inflation with a case study of onion and cayenne pepper commodity prices in Malang City since 2011 until 2016. The analytical method used was Partial Adjustment Model (PAM) and Clasical Assumption Test. The used data in this research was secondary data that got from various sources such as Central Bureau of Statistics (BPS) and Availability of Information System and Development of Basic Materials Prices (Siskaperbapo) East Java. The result of this research showed that result of the long run equation test PAM of onion had significant effect and cayenne had significant effect on inflation. On result of the short run equation test PAM of onion and cayenne pepper had significant effect on inflation in Malang City.